Nordic Relief Packages and Non-standard Workers: Towards Expanded Universalism and Institutional Inequalities - Larsen, Trine P.; Ilsøe, Anna (Aalborg University, Denmark, 2022)
Has the Corona crisis triggered changes to Nordic social protection? We address this question by examining how Denmark, Finland, Norway, Finland, Iceland, and Sweden reacted to the crisis, which in many ways resembles a Litmus-test for Nordic social protection. Analytically, we draw on historical institutionalism, welfare, and segmentation literature. We find that although the Nordic relief packages aim to create an encompassing safety net, the reforms expose and sometimes reinforce institutionally embedded cracks in the Nordic systems around the nexus of standard and non-standard work, leading to potential layers of institutionally embedded inequalities. The Nordic countries have expanded and adjusted their existing social protection, portraying strong elements of path dependency, but with examples of novel initiatives. Their mix of universal and targeted measures appears to reflect so-called ‘expanded universalism’, where targeted measures supplement the ‘ordinary’ Nordic social protection to cover the most crisis ridden, but not necessarily the poorest, groups.